Urban Societies in East-Central Europe, 1500–1700 - Miller, Jaroslav (2013)
Whilst much has been written about early modern urban history, the majority of this work has focussed on Western Europe with relatively little available in English on towns and cities in the former communist East. However, in recent years urban scholars have increasingly looked to a much more inclusive picture of Europe that compares and contrasts development across the whole continent. Dealing primarily with Bohemia, Hungary and the Polish-Lithuanian Commonwealth, this book provides an insight into a number of key issues concerning the economic, social and demographic trends in early modern East-Central European urban history. Taking a supra-national perspective, across a long time span, it examines the effects of migration, Reformation, state building and economic change on the transformation of medieval urban communities into early modern societies. Drawing on a wealth of primary sources, particularly the registers of new citizens kept by many towns and cities, a fascinating picture of urban development and social structure is reconstructed that not only tells us much about East-Central Europe, but adds to our knowledge of the whole continent.